Genetic Diversity in HIV-1 Subtype C LTR from Brazil and Mozambique Generates New Transcription Factor-Binding Sites - Boullosa, José (MDPI, 2014)
The HIV-1 subtype C has been substituting the subtype B population in southern Brazil. This phenomenon has been previously described in other countries, suggesting that subtype C may possess greater fitness than other subtypes. The HIV-1 long-terminal repeat (LTR) is an important regulatory region critical for the viral life cycle. Sequence insertions immediately upstream of the viral enhancer are known as the most frequent naturally occurring length polimorphisms (MFNLP). Previous reports demonstrated that the MFNLP could lead to the duplication of transcription factor binding sites (TFBS) enhancing the activity of the HIV-1 subtype C LTR. Here, we amplified and sequenced the LTR obtained from proviral DNA samples collected from patients infected with subtype C from the Southern Region of Brazil (naïve or treatment failure) and Mozambique (only naïve). We confirm the presence of different types of insertions in the LTR sequences of both the countries leading to the creation of additional TFBS. In the Brazilian clinical samples, the frequency of the sequence insertion was significantly higher in subjects experiencing treatment failure than in antiretroviral naïve patients.